Chronic kidney disease stage stratifies short- and long-term outcomes after aortic root replacement. (30th December 2020) - Yamabe, Tsuyoshi; Zhao, Yanling; Kurlansky, Paul A; Nitta, Suzuka; Kelebeyev, Saveliy; Bethancourt, Casidhe-Nicole R; George, Isaac; Smith, Craig R; Takayama, Hiroo
Abstract: OBJECTIVES: Chronic kidney disease (CKD) is prevalent in patients undergoing cardiovascular surgery, and it negatively impacts procedural outcomes; however, its influence on the outcomes of aortic surgery has not been well studied. This study aims to elucidate the importance of CKD on the outcomes of aortic root replacement (ARR). METHODS: Patients who underwent ARR between 2005 and 2019 were retrospectively reviewed ( n  = 882). Patients were divided into 3 groups based on the Kidney Disease: Improving Global Outcomes criteria: Group 1 [estimated glomerular filtration rate (eGFR) ≥ 60 ml/min/1.73 m 2, n  = 421); Group 2 (eGFR = 30–59 ml/min/1.73 m 2, n  = 424); and Group 3 (eGFR < 30 ml/min/1.73 m 2, n  = 37). To reduce potential confounding, a propensity score matching was also performed between Group 1 and the combined group of Group 2 and Group 3. The primary end point was 10-year survival. Secondary end points were in-hospital mortality and perioperative morbidity. RESULTS: Severe CKD patients presented with more advanced overall chronic and acute illnesses. Kaplan–Meier analysis showed a significant correlation between CKD stage and 10-year survival (log-rank P < 0.001). The number of events for Group 1 was 15, Group 2 was 49 and Group 3 was 11 in 10 years. Group 3 had significantly higher in-hospital mortality (13.5% vs 3.5% in Group 2 vs 0.7% in Group 1, P < 0.001) and stroke (8.1% vs 7.1% vs 1.2%, P < 0.001) as well as introduction to new dialysis (27.0% vs 5.4% vs 1.7%, P < 0.001). eGFR was shown to be an independent predictor of mortality (hazard ratio, 0.98; 95% confidence interval, 0.96–0.99). Comparison between propensity matched groups showed similar postoperative outcomes, and eGFR was still identified as a predictor of mortality (hazard ratio, 0.97; 95% confidence interval, 0.95–0.99). CONCLUSIONS: Higher stage in CKD negatively impacts the long-term survival in patients who are undergoing ARR.